Implementation of Problem-Based Learning with a Connected Approach in Indonesian Language Learning in Grade III Elementary School: A Qualitative Descriptive Study - Ginanjar, Dede; Sutini, Ai (International Conference on Elementary Education, 2025)
Indonesian language learning in elementary schools requires strategies that can enhance student engagement, comprehension, and critical thinking skills. The Problem-Based Learning (PBL) model with a Connected approach allows students to relate the learning material to real-life experiences, promoting active and meaningful learning. This study aims to describe the implementation of the PBL model with a Connected approach in Indonesian language learning for third-grade elementary school students, including the learning process, student participation, and challenges encountered. The research used a descriptive study with a qualitative approach. The subjects were third-grade students at one elementary school, and data were collected through participatory observation, interviews with teachers and students, and documentation of learning activities. Data analysis was conducted qualitatively through data reduction, data display, and conclusion drawing. The results showed that the implementation of PBL with a Connected approach followed the stages of problem identification, group discussion, problem solving, and reflection. Students actively participated, were able to connect the material to daily experiences, improved critical thinking skills, and enhanced communication abilities. Challenges included limited time and differences in students’ readiness to understand the problems. In conclusion, the PBL model with a Connected approach is effectively implemented in third-grade Indonesian language learning, increasing student engagement, comprehension, and critical thinking, while providing a foundation for teachers to develop contextual and meaningful learning strategies.